Bimbingan Kelompok Ibu Bekerja Efektifitas Layanan Bimbingan Kelompok dengan Teknik Self Management pada Ibu Bekerja denganAnak Usia Remaja Awal di Kampung Togaten - Galuh Ayu Mustikasari; Anzar Aquil (State Islamic University (UIN) Salatiga, 2024)
This study aims to examine the effectiveness of group guidance services utilizing self-management techniques in reducing stress levels in Muslim mothers who work and have early adolescent children. The type of research used was experimental research. The research sample was 12 subjects at high-stress levels determined by a proportionate stratified random sampling technique with an error tolerance of 5%. Subjects were divided into two groups with different treatments. The experimental group was given group guidance services using self-management techniques, and the control group was given guidance services using lecture techniques. The instrument used was a stress scale with 11 items adapted from the Depression, Anxiety, and Stress Scalle-42 (DASS-42) (Lovibond & Lovibond, 1995) with a reliability of .891. Data were analyzed using the Mann-Whitney U test with a p-value = .002 (p<.05). The results showed a significant post-test difference between the stress levels of the experimental group and the control group, so it was concluded that group guidance utilizing self-management techniques was effective for reducing stress levels in working Muslim mothers with early adolescent children.